2018
DOI: 10.1093/mnras/sty489
|View full text |Cite
|
Sign up to set email alerts
|

The connection between mass, environment, and slow rotation in simulated galaxies

Abstract: Recent observations from integral field spectroscopy (IFS) indicate that the fraction of galaxies that are slow rotators, F SR , depends primarily on stellar mass, with no significant dependence on environment. We investigate these trends and the formation paths of slow rotators (SRs) using the EAGLE and HYDRANGEA hydro-dynamical simulations. EAGLE consists of several cosmological boxes of volumes up to (100 Mpc) 3 , while HYDRANGEA consists of 24 cosmological simulations of galaxy clusters and their environme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
130
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(153 citation statements)
references
References 87 publications
22
130
1
Order By: Relevance
“…z > 1.0), (cosmological) numerical simulations will allow us to explore the evolution of angular momentum with time (e.g. Lagos et al 2018;Schulze et al 2018;Pillepich et al 2019 For an oblate galaxy, viewed at inclination i, we obtain…”
Section: Discussionmentioning
confidence: 99%
“…z > 1.0), (cosmological) numerical simulations will allow us to explore the evolution of angular momentum with time (e.g. Lagos et al 2018;Schulze et al 2018;Pillepich et al 2019 For an oblate galaxy, viewed at inclination i, we obtain…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the notion that rotationally supported galaxies should have had quiescent accretion histories, and consequently lower f M * ,IHSC . Lagos et al (2018b) found that the highest V/σ galaxies can only be obtained in the absence of mergers. On the other hand, a dispersion-supported galaxy is expected to have experienced multiple mergers and interactions, which in turn should deposit higher amounts of mass into the IHSC, increasing its f M * ,IHSC .…”
Section: Kinematic Morphologymentioning
confidence: 99%
“…Simulations find that mergers impart a cumulative effect, and galaxies that have experienced successive multiple mergers are more likely to have lower spins (Lagos et al 2018). Furthermore, slow-rotating remnants from multiple mergers of disc galaxies are more likely to show kinematics twists, while remnants from binary mergers most often do not (Moody et al 2014).…”
Section: Discussionmentioning
confidence: 99%